REAL TIME IMPLEMENTATION OFNONLINEAR PI CONTROLLER FOR THE INDUCTION MACHINE CONTROL - Habbab, M; Hazzab, A; Alalei, A (university of eloued -جامعة الوادي, 2019)
n this paper a nonlinear PI (NPI) controller are proposed and compared with the conventional linear fixed-gain PI controller to improve the overall performance of the system by incorporating a sector-bounded nonlinear gain in cascade with a conventional PI control architecture. The proposed controller has implemented for a 1.5-kW three-Phase Induction Motor are completely carried out using a dSPACE DS1104 digital signal processor (DSP) based real-time data acquisition control (DAC) system, and MATLAB/Simulink environment. Digital experimental results are presented to show the improvement in performance of the proposed algorithm
article
Keywords: PI controller; Nonlinear PI controller; Induction Machine; IFOC; dSPACE